Automação e monitoramento de um sistema de aproveitamento de águas pluviais para utilidades não potáveis - Brasil, Gleimy Ferreira (Universidade Federal Rural do Semi-Árido, 2018)
The present work demonstrates the operation of a prototype that seeks to simulate automation of a rainwater harvesting system, using three plastic reservoirs, wooden base and a funnel, representing the system of abstraction, storage and distribution of water for non-potable purposes. The automation was developed with electromechanical devices along with the logical development, where an Atmega 328p microcontroller was used, determining the functions of each device according to the situation that the system presents itself. The main objective of the work was to develop an automated and efficient prototype with the purpose of making use of rainwater, seeking to reduce the use of drinking water for less noble purposes such as discharges, watering gardens and washing sidewalks. We can say that the rest were very satisfactory since the system as a whole responded according to the expected for all the situations predicted. The pump and the solenoid valves acting correctly together with the level sensors. In view of this we can see the importance of the development of the project, contributing to a sustainable consumption of water, a small financial economy and reducing residential routines.
Artigo Acadêmico
Keywords: Automação residencial; Águas pluviais; Água; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA